Reflections on the intercultural politics of food, diet, and nutrition research in Canadian Inuit communities - Fletcher, Christopher (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2016)
This essay explores the intercultural dynamics of food and health research in Inuit communities over time. Multiple sources of information are used to explore Inuit subjectivity in research through different ways of conceptualizing and acting on food-related practice and knowledge. How people experience being the subject of research, how that research mobilizes knowledge and resources, and how these in turn feed back into the larger social field is an important part of an intercultural dynamic in the Inuit Nunangat. Scientific interest in the Inuit diet is among the oldest of preoccupations in the health field, stretching back to the earliest encounters of Europeans with Inuit. Today, diet-related health issues are still a major area of scientific investigation and public health intervention. A deeper consideration of both Inuit and researcher cultures in food and diet-related health research will lead to more effective health promotion activities in Inuit communities.